2021
DOI: 10.3389/fcimb.2021.628887
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of AGO-Associated Zika Virus-Derived Small Interfering RNAs in Neural Stem Cells

Abstract: Viral interfering RNA (viRNA) has been identified from several viral genomes via directly deep RNA sequencing of the virus-infected cells, including zika virus (ZIKV). Once produced by endoribonuclease Dicer, viRNAs are loaded onto the Argonaute (AGO) family proteins of the RNA-induced silencing complexes (RISCs) to pair with their RNA targets and initiate the cleavage of target genes. However, the identities of functional ZIKV viRNAs and their viral RNA targets remain largely unknown. Our recent study has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Only when loaded into Argonaute (AGO), siRNAs and miRNAs perform their functions. Hence, Zeng et al (2021) constructed AGO-associated viral siRNA profiles and completed a network between ZIKV siRNAs and their probable viral RNA (vRNA) targets via AGO-associated RNA sequencing. Twenty-nine siRNAs and 114 potential targets were obtained from the ZIKV genome, and further functional characterization of ZIKV siRNAs need to be verified.…”
Section: Other Non-coding Rnas During Flavivirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only when loaded into Argonaute (AGO), siRNAs and miRNAs perform their functions. Hence, Zeng et al (2021) constructed AGO-associated viral siRNA profiles and completed a network between ZIKV siRNAs and their probable viral RNA (vRNA) targets via AGO-associated RNA sequencing. Twenty-nine siRNAs and 114 potential targets were obtained from the ZIKV genome, and further functional characterization of ZIKV siRNAs need to be verified.…”
Section: Other Non-coding Rnas During Flavivirus Infectionmentioning
confidence: 99%
“…In addition, the virus itself produces a variety of non-coding RNAs, such as subgenomic flaviviral RNAs (sfRNAs) and viral small RNAs (vsRNAs), the latter also include viral small interfering RNAs (siRNAs) and virus-encoded miRNAs. All of them can interact with cellular and viral RNA to regulate flavivirus replication ( Schuessler et al, 2012 ; Hussain and Asgari, 2014 ; Zeng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once produced, vsiRNAs are loaded onto AGO family proteins of the RISCs to initiate the cleavage of host target genes and cognate viral RNAs (Guo et al, 2019). ZIKV infection has been demonstrated to induce abundant vsiRNAs in NSCs and hNPCs (Xu et al, 2019;Zeng et al, 2021). Zeng et al reported not only that vsiRNA is a limiting factor for ZIKV infection in NSCS, but also that the total 29 vsiRNAs across the ZIKV genome through AGO-associated RNA-seq.…”
Section: Zikv Infection Induces Anti-viral Small Interfering Rnas In Pluripotent Cellsmentioning
confidence: 99%
“…Once produced, vsiRNAs are loaded onto AGO family proteins of the RISCs to initiate the cleavage of host target genes and cognate viral RNAs ( Guo et al., 2019 ). ZIKV infection has been demonstrated to induce abundant vsiRNAs in NSCs and hNPCs ( Xu et al., 2019 ; Zeng et al., 2021 ). Zeng et al.…”
Section: Zikv Infection Induces Anti-viral Small Interfering Rnas In Pluripotent Cellsmentioning
confidence: 99%
See 1 more Smart Citation